EFEITO DA DENSIDADE DE PLANTAS SOBRE O COMPORTAMENTO DE DOIS CULTIVARES DE SOJA - Nakagawa, João; Rosolem, Ciro Antonio; Machado, José Ricardo (REVISTA DE AGRICULTURA, 2015)
EFEITO DA DENSIDADE DE PLANTAS SOBRE O COMPORTAMENTO DE DOIS CULTIVARES DE SOJA